(3TQM aUhd CHbQGWs - (3YdGA GdOjf , Ydj Hf CHi GdMRe GdbQTi , GHf GdfajSs; (3GHbQGW GdMcjes ((3GdbGgQI s)
(3ChdgG (B:s
(3CeG HYO(B: (3aEfeG bO SdeJ ef TQhMfG dgPG GdcJGH , aEf fSNI JNJda HMSH dCCZQGV GdcJGH s
(3BNQgG (B:s
(3heJi cGf cPdc hLH Cf jchf GdESJaQGZ hGdbF ; hgPG GdeQGO HGdESJaQGZ ef ahb adfNJe GdcJGH s
(3aUd ajgG Hjf bhd CHbQGW hTQM GHf GdfajS HGdYfGhjf JSgjdkG hJjSjQkGs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdWHs